Team Engagement and Performance Management (A Study of Banking Industry) - Ida Ayu Rusmahadewi; Gede Sri Darma (Universitas Pendidikan Nasional, 2018)
ABSTRACTThis research aims to find out how the strategy to increase the value of PT. Bank Central Asia (Persero) Tbk.,abbreviated BCA’s performance, and to look for alternative strategies to maintain BCA’s performance going forward.Data collection techniques by interviewing informants, namely the branch head of Bank BCA Denpasar by an independent interviewer, were also observed with an undercover strategy considering the researcher was a full participant. The analysis that researcher use is a qualitative descriptive data analysis technique with the Miles and Hubermanmodels.The results show that the team's role is huge, in this case team engagement that contributes greatly to the success of BCA Denpasar in achieving success in 2017. The teamengagement is a part of corporate values (BCA’s values) that are derived from the vision and mission of BCA. Management tries to overcome the previous obstacle of team communication that resulted in the previous team failed to achieve good value in a performance appraisal (performance appraisal of a branch office or the PKKC). Future research is expected to quantitatively measure significant or not implementation of strategy and decision management strategy to the performance either directly or indirectly in improving organizational performance.